Implementing Tablet-Based Devices to Improve Communication Skills of Students With Autism. (September 2017) - Alzrayer, Nouf M.; Banda, Devender R.
Students with autism spectrum disorder (ASD) have difficulties in communication that limit their opportunities to participate in daily living and educational activities. Augmentative alternative communication is one of the strategies used to strengthen the communication skills of students with limited communication skills. Students with ASD commonly use handheld devices for communication. This article provides guidelines for special education teachers to support the implementation of tablet-based speech-generating devices in their classrooms. These guidelines may help special education teachers through the process of creating a student's profile, conducting preference assessments, programming devices, and providing instruction in natural contexts.